Web based application for low-cost food tourism in Perlis / Amir Farhan Saupi - Saupi, Amir Farhan (2019)
The rise of the experience economy has ushered in a growing role for food experience in tourism. This review of recent developments in the field of food and tourism experiences underlines the ways in which food experiences can be adapted to meet tourist needs, how it can play a role in local development, create new tourism products, stimulate innovation and support marketing and branding. Nowadays low-cost food tourism sector is considered to be one of the most important sectors of tourism. Low-cost food usually operated and works out by local people which have lower financial income to start a business. The low-cost food sector is becoming a valuable part of tourism. Despite on this, this paper presents an explanatory study of using Network Analyst operation and develops a web-based application for low-cost food tourism. The low-cost food location usually scattered and by using Network Analyst, it can identify the location and can provide it the best route to it location. The result of this study explained how network analyst can help to improve the low-cost food tourism and provide a web-based application for tourism marketing.